PENURUNAN BOD DAN COD LIMBAH CAIR INDUSTRI TEKSTIL DI KABUPATEN PEKALONGAN DENGAN METODE MULTI SOIL LAYERING - Irmanto Irmanto; Suyata Suyata (Molekul, 2008)
Multi Soil Layering (MSL) system is a method of wastewater treatment that increase the soils function to purify wastewater. In the construction of MSL, soils mixed with the charcoal and then filled into the box of size 50x14x50 cm in layers structured like brick pattern. The aims of this research are to determine the concentration of BOD and COD on textile industrial wastewater before and after the process by MSL method. It also determines the optimal loading rate of wastewater on the MSL system, and then it can determine the efficiency of MSL system on reducing the concentration of BOD and COD on textile industrial wastewater. The method which used in this research is an experimental method. The wastewater on the MSL system is loaded on the loading rate variety: 160, 320, 480, 640, and 800 L m-2 day-1. The efficiency of MSL system to removing BOD and COD on textile industrial wastewater are determined on optimal loading rate. The research gave result that MSL method could remove BOD and COD on textile industrial wastewater on the optimal loading rate 320 L m-2 day-1. The efficiency of MSL system in removing BOD and COD on textile industrial wastewater are 96.52 and 80.87% respectively. This indicated that the method MSL serve the purpose of effective alternative method in processing of liquid waste textile industry.